Mechanical Properties Investigation of Composite Material Under Different Parameters Variations - Mohammed, Farag M. (Al-Khwarizmi Engineering Journal, 2017)
The main objective of this research is to design and select a composite plate to be used in fabricating wing skins of light unman air vehicle (UAV). The mechanical properties, weight and cost are the basis criteria of this selection. The fiber volume fraction, fillers and type of fiber with three levels for each were considered to optimize the composite plate selection. Finite element method was used to investigate the stress distribution on the wing at cruise flight condition in addition to estimate the maximum stress. An experiments plan has been designed to get the data on the basis of Taguchi technique. The most effective parameters at the process to be find out by employing L9 (33) orthogonal array, signal to noise ratio (S/N), main effect and analysis of variance (ANOVA). The results show that, the experimental and the predicted results are very close. It was found that the type of fiber is the most effective parameter on the plate selection, followed by filler content and then the fiber volume fraction. The best parameters combinations are ((E-glass woven roving + unidirectional carbon) fiber, 7.5% graphite filler and 30% fiber volume fraction). This combination provides good mechanical properties, high safety factor, acceptable cost, and offers weight savings on average by 40% percent as compared to aluminum alloy.